Numerical Simulation of Thermal Fields and Microstructure Evolution in SLM of Fe32Cr33Ni29Al3Ti3 Alloy - Xuyun Peng; Xiaojun Tan; Haibing Xiao; Wei Zhang; Liang Guo; Wei Tan; Jian Huang; Chaojun Ding; Yushan Yang; Jieshun Yang; Haitao Chen; Qingmao Zhang (Micromachines)
Fabricating eutectic high-entropy alloys (EHEAs) via selective laser melting (SLM) presents significant potential for advanced structural applications. This study explores the microstructural evolution of Fe32Cr33Ni29Al3Ti3 EHEAs fabricated by SLM under varying laser powers. Electron backscatter diffraction (EBSD) analysis revealed that samples fabricated at 200 W exhibited approximately 70% face-centered-cubic (FCC) and 30% body-centered-cubic (BCC) phases. In comparison, those processed at 160 W showed an increased FCC fraction of 85% with a corresponding reduction in BCC content. Grain size measurements indicated that BCC grains were consistently finer than their FCC counterparts. Thermal simulations demonstrated that higher laser power produced deeper melt pools and broader temperature gradients. By correlating thermal history with phase diagram data, the spatial variation in BCC content was attributed to the differential residence time in the 1350–1100 °C range. This study represents one of the first attempts to quantitatively link local thermal histories with the evolution of dual-phase (FCC + BCC) microstructures in EHEAs during SLM. The findings contribute to the improved understanding and control of phase formation in complex alloy systems, providing valuable guidance for tailoring SLM parameters to optimize the phase composition and microstructure of EHEAs.